Use of Urethral Sound to Facilitate Locating Retrovesical Ureter for Politano-Leadbetter Pneumovesicoscopic Ureteral Reimplantation - Zhao, Xiang; Tian, Qingqing; Fang, Erhu; Li, Ning (Frontiers in Pediatrics, 2022)
Abstract Backgrounds: Pneumovesicoscopic ureteral reimplantation (PVUR) has gained popularity due to its minimal invasiveness. However, most of the reported PVUR procedures were based on the Cohen technique. Only few studies reported their experience of PVUR using Politano-Leadbetter technique (PVUR-PL). Here, we reported our experience of PVUR-PL using a novel technique to facilitate locating the retrovesical ureter during the procedure. Materials and Methods: The medical records of the patients who underwent PVUR-PL between January 2018 and December 2020 in our institution were retrospectively reviewed. The patients were classified into two groups: the modified group that accepted PVUR-PL using our novel technique (using of urethral sound to facilitate identifying the retrovesical ureter) and the traditional group that accepted PVUR-PL not using the novel technique. Clinical data were collected retrospectively. Results: There were 22 patients underwent PVUR-PL with 13 in the traditional group and nine in the modified group. The mean operating time for unilateral cases in the modified group was significantly shorter than that in the traditional group (154.5 versus 195.5 minutes, p < 0.001). For bilateral cases, the mean operating time was also significantly reduced (from 263.0 to 221.3 minutes, p = 0.022) in the modified group. There were no severe complications occurred in each of the two groups. The peritoneum was perforated in one case from the traditional group, while no peritoneum perforation occurred in the modified group. Conclusion: Using of urethral sound to help to identify the retrovesical ureter during PVUR-PL is a safe and effective technique. This simple but effective technique could shorten the operating time of PVUR-PL and reduce the risk of peritoneum perforation.